AGRICULTURAL LAND USE structural transformations,environment challenges. (ROUTLEDGE, 2025)
This book presents contemporary trends and challenges in agricultural land use, drawing on an array of global case studies.This volume examines agricultural land use through a three-pronged approach: structural transformations, environmental challenges, and planning and policy. Reflecting the global relevance of contemporary challenges to agricultural land use, the book presents a wide range of novel case studies from across the world, including Poland, Hungary, Denmark, Slovenia, Czechia, Tanzania, Uganda, South Africa, Algeria, Northeast Africa countries, China, India, Australia, New Zealand, USA, and Brazil. Each chapter focuses on a particular issue related to agricultural land use in that country or region, including land fragmentation, reduction of crop land, agricultural intensification, desertification of soils, climate change, biodiversity loss, traditional agricultural systems, urbanization and rural development, and planning challenges for agricultural land. Together the chapters present a global view of the challenges facing the agricultural industry and offer solutions for developing sustainable agricultural practices to ensure food security and environmental and biodiversity conservation.This book will be of great interest to students and scholars of food and agriculture, land use and land management, rural studies, and sustainable development.
Keywords: Land use, Rural.; Agriculture -- Environmental aspects.; Land capability for agriculture.; elektronické knihy; electronic books